Importance of Breast Sensation After Mastectomy: Evidence from Three Sources - Stacy T. Lindau; El A. Pinkerton; Emily M. Abramsohn; Charles M. Fuller; Danielle Grubb; Tania Mendoza; Amy K. Siston (Mary Ann Liebert, 2023)
Background: Every year, more than 90,000 U.S. women undergo mastectomy. More than 40% have reconstruction. Following reconstruction, most women experience persistent partial or complete numbness of the reconstructed breasts, and many experience pain. Yet, breast reconstruction procedures focus largely on esthetic outcomes with mixed impact on sensory outcomes and little attention to pain. This study examines whether and how breast sensation is important to women. Materials and Methods: Conventional content analysis of extant qualitative data from a clinical registry (29 women with prior breast surgery for cancer, 2008?2022), a volunteer community sample (qualitative interviews with 6 women with and 5 without breast cancer, 2019), and from a Twitter social media survey (N?=?32, 2022). Results: Functions of the breast identified by women with and without cancer include breastfeeding, sexual function, and femininity. Five interrelated themes on the importance of breast sensation emerged among women with breast cancer history: sexual function, experience of partnered sex or relationship with one's sexual partner, breast embodiment, effect of breast pain on sexual function, and importance to psychological wellbeing. Women, advocates, and clinicians described a lack of patient?physician communication in this domain that exacerbates the negative impact of breast sensation loss on health and wellbeing. Conclusions: Breast sensation is important to women following mastectomy, yet a gap exists in patient?physician communication about the impact of mastectomy and reconstruction on breast sensory function. Lessons for physicians, scientists, and skeptics are conveyed about why the basic integrity of women's bodies matters for practice and science.